Advancing Tetrazine Bioorthogonal Reactions through the Development of New Synthetic Tools - Devaraj, Neal K. (Synlett, 2012)
There has been increasing interest in the use of tetrazines as partners in bioorthogonal inverse Diels–Alder cycloadditions. Although tetrazine cycloadditions possess several characteristics that make them attractive compared to alternative coupling strategies, the coupling partners, 1,2,4,5-tetrazines and strained alkenes and cycloalkynes, are not trivial to synthesize. The use of tetrazines and dienophiles in biological applications has required the development of new synthetic methodologies to create stable yet reactive probes conveniently. This paper addresses the synthetic milestones that have enabled and improved tetrazine cycloadditions as a popular form of bioorthogonal chemistry and highlights recent work from our lab that we believe has advanced the methodology available for the synthesis of tetrazines1 and smaller strained cyclopropene dienophiles.2 We also outline some future challenges and open questions that remain to be addressed.
Keywords: cycloaddition; Diels–Alder reaction; bioorganic chemistry; self-assembly; coupling